INVESTIGATION OF METAL CHIP HEATING PROCESS (Part 2) - O. M. Dyakonov (Наука и техника)
A physical and mathematical model of metal chip heating process in a continuous muffle furnace has been worked out. The model describes a conjugated heat- and mass transfer in the given  furnace (conductive, convective, radiant), heating of chips and furnace parts, lubricant-coolant evaporation, oil vapour combustion, flue gas movement. The received set of equations is a completed one that allows to solve a specified problem that is to find an optimum height for a furnace with the given productivity  and minimum natural gas consumption.